Al Saj’u fī Kitābi al Ḍiyā’i al Lāmi’i (Dirāsatun fī ‘Ilmi al Badī’i) - Litasari, Desi; Fahri, Ismail (Al-Uslub: Journal of Arabic Linguistic and Literature, 2021)
This study aims to find out the kinds of things in the addiyaullami book, to know the purpose of the poems in the addiyaullami book. This research was conducted using a qualitative method with a descriptive approach. The data source of this research is the addiyaullami' book. Data collection techniques used are reading and note-taking techniques. The type of research used is literature review. There are two sources of data used, the first primary data source used is the book addiyaullami 'by Habib Umar bin Muhammad bin Salim bin Hafidz bin Sheikh bin Abi Bakri bin Salim. Meanwhile, the secondary data sources used are books and journals related to the topic of this research. The results of this study indicate that there are rhyme three kinds of 'addiyaullami', namely 'mutorrof, rhyme muttawazi and rhyme murasa' whichever mutorof there are as many as thirty fasilah then alone mutawazi there are eight fasilah and rhyme murassa' there is as much as one fasilah. Rhyme the most' are 'muttorofs and all types rhyme that were studied amounted to rhyme thirty-nine. Then the purpose of the poems in the addiyaullami' book contains thirty-one al-maddah, five al-fahri, thirteen al-hikmah, one al-i'tidzar, one al-hamasah, one al-wasfi. and al-Hamasah as much as one.